Happiness adaptation to income and to status in an individual panel - Di Tella, Rafael 1965-; Haisken-DeNew, John P. 1965-; MacCulloch, Robert (Working paper series / National Bureau of Economic Research, 2007)
We study "habituation" to income and to status using individual panel data on the happiness of 7,812 people living in Germany from 1984 to 2000. Specifically, we estimate a "happiness equation" defined over several lags of income and status and compare the long run effects. We can (cannot) reject the hypothesis of no adaptation to income (status) during the four years following an income (status) change. In the short-run (current year) a one standard deviation increase in status and 52% of one standard deviation in income are associated with similar increases in happiness. In the long-run (five year average) a one standard deviation increase in status has a similar effect to an increase of 285% of a standard deviation in income. We also present different estimates of habituation across sub-groups. For example, we find that those on the right (left) of the political spectrum adapt to status (income) but not to income (status).